BODY FAT PROFILE AND METABOLIC DISORDERS BETWEEN MILITARIES OF II CENTER OF AIR DEFENSE AND CONTROL OF AIR TRAFFIC CINDACTA II (CURITIBA-PR) (Fiep Bulletin - online, 2015)
This study intended to verify the profile of the human body fat in adult militaries of both sexes and the risks of metabolic alterations. The Body Mass Index (BMI), Waist Circumference (WC) and the Ratio Waist-to-Hip (WHR) were checked in 835 members of the military base (AMERICAN COLLEGE OF SPORTS MEDICINE, 2006, LARSSON, 1984). In a general way the militaries subject to the research presented normal BMI, WC and WHR relations, which means they are have little tendencies at all to develop diseases associated to metabolic disorders. Statistically significant differences were noticed between men and women. It has been so due to the fact that the men tested present higher concentrations of abdominal fat, and that is a decisive factor when measuring WHR scores.
Keywords: body fat profile; health; metabolic alterations.